The Usually Invisible, Occasionally Visible, Spirits of the Dead in Early Twentieth-Century Sámi Folklore - Thomas A. DuBois (Humanities, 2023)
Turn-of-twentieth-century Sámi concepts of spirits of the dead are presented along with accounts of those exceptional individuals able to see, hear, interact with, and sometimes control them, particularly persons termed noaideslágáš, i.e., skilled in noaidi arts. Examples and analysis are drawn from the writings of Sámi author and scholar Johan Turi (1854–1936), contemporaneous accounts recorded by Norwegian folklorist Just Qvigstad (1853–1957), the fieldwork of Sámi legislator, educator, and folklore collector Isak Saba (1875–1921), and an 1886 anthology of Aanaar (Inari) Sámi folklore. Described with varying names and sometimes contradicting accounts, the spirits of the dead in Sámi culture during the early twentieth century could be used to protect or enhance the fortunes of the living, but could also play roles in situations of disease, misfortune, and interpersonal conflict. The various narratives recorded in the period reflect a complex fusion of Indigenous Sámi traditions with ideas stemming from various Christian denominations and the belief legends of non-Sámi neighbors in the Finnish, Norwegian, Russian and Swedish sides of Sápmi—the Sámi homeland. Spirits of the dead figure as potent, expectable, but sometimes unpredictable elements of daily life—beings that could help or harm, depending on how they were dealt with by those with whom they came in contact and those who could wield power over them, particularly noaiddit, Sámi ritual and healing specialists.